DIGITAL TRANSFORMATION OF DIVORCE CERTIFICATES AND REFORM OF RELIGIOUS COURT PROCEDURE IN INDONESIA - Ana Laela Fatikhatul Choiriyah; Inayatul Anisah; Yudha Bagus Tunggal Putra (Indonesian Journal of Shariah and Justice, 2025)
The implementation of the Electronic Divorce Certificate within the Religious Court system through Decree of the Director General of Badilag Number 932/DJA/SK.TI1.3.3/VII/2025 represents a strategic innovation in the digitalization of legal services. This policy is in line with the principle of a simple, fast, and low-cost judiciary, as mandated by Law Number 48 of 2009 on Judicial Power. Through the EAC, the administrative process of divorce is expected to become more efficient and transparent, while also reducing bureaucratic complexity and the risk of misuse of physical documents. From the perspective of Islamic civil procedural law, the EAC remains legally valid provided that it complies with divorce registration procedures conducted by authorized officials and is based on a court decision that has obtained permanent legal force. The legality of the EAC is further reinforced by Law Number 11 of 2008 on Electronic Information and Transactions, particularly Article 5 paragraph (1), Articles 14, and 15, which recognize electronic documents as legally valid evidence, provided that they meet the principles of authenticity, integrity, and reliability of electronic systems. Nevertheless, the implementation of the EAC requires harmonization with the principles of legal protection and personal data protection, as regulated under Law Number 27 of 2022. The protection of sensitive personal data of the parties involved constitutes a crucial aspect that must be ensured through reliable technological security systems. With this approach, the EAC has the potential to deliver a modern and effective religious court service while safeguarding the legal rights of justice seekers.